Social Network Types Among Polish Senior Citizens and Perception of the Quality of Their Lives - Kozerska, Agnieszka (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The objective of this paper is to establish social network typologies of Polish elderly people based on empirical data. Moreover, the aim is to determine the frequency of occurrence of particular network types in Poland and examine the association between the distinguished social network types and older people’s perceptions of the quality of their lives. The analysis was conducted using data collected in 2013 and is available on www.diagnoza.com. The data concerns 9673 Polish senior citizens. The cluster analysis was used to form groups of people participating in the analysis. The following three types of social networks among Polish seniors were identified: “diverse”, “family and friends” as well as “restricted”. The restricted type constitutes the most numerous group but it is characterized by the lowest level of well-being. However, the elderly belonging to the diverse network are found to be the most satisfied with the quality of their lives.